(7x-5yi)-(9-4i)=-2i+15

Simple and best practice solution for (7x-5yi)-(9-4i)=-2i+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-5yi)-(9-4i)=-2i+15 equation:


Simplifying
(7x + -5yi) + -1(9 + -4i) = -2i + 15

Reorder the terms:
(-5iy + 7x) + -1(9 + -4i) = -2i + 15

Remove parenthesis around (-5iy + 7x)
-5iy + 7x + -1(9 + -4i) = -2i + 15
-5iy + 7x + (9 * -1 + -4i * -1) = -2i + 15
-5iy + 7x + (-9 + 4i) = -2i + 15

Reorder the terms:
-9 + 4i + -5iy + 7x = -2i + 15

Reorder the terms:
-9 + 4i + -5iy + 7x = 15 + -2i

Solving
-9 + 4i + -5iy + 7x = 15 + -2i

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '2i' to each side of the equation.
-9 + 4i + -5iy + 2i + 7x = 15 + -2i + 2i

Reorder the terms:
-9 + 4i + 2i + -5iy + 7x = 15 + -2i + 2i

Combine like terms: 4i + 2i = 6i
-9 + 6i + -5iy + 7x = 15 + -2i + 2i

Combine like terms: -2i + 2i = 0
-9 + 6i + -5iy + 7x = 15 + 0
-9 + 6i + -5iy + 7x = 15

Add '9' to each side of the equation.
-9 + 6i + -5iy + 9 + 7x = 15 + 9

Reorder the terms:
-9 + 9 + 6i + -5iy + 7x = 15 + 9

Combine like terms: -9 + 9 = 0
0 + 6i + -5iy + 7x = 15 + 9
6i + -5iy + 7x = 15 + 9

Combine like terms: 15 + 9 = 24
6i + -5iy + 7x = 24

Add '-7x' to each side of the equation.
6i + -5iy + 7x + -7x = 24 + -7x

Combine like terms: 7x + -7x = 0
6i + -5iy + 0 = 24 + -7x
6i + -5iy = 24 + -7x

Reorder the terms:
-24 + 6i + -5iy + 7x = 24 + -7x + -24 + 7x

Reorder the terms:
-24 + 6i + -5iy + 7x = 24 + -24 + -7x + 7x

Combine like terms: 24 + -24 = 0
-24 + 6i + -5iy + 7x = 0 + -7x + 7x
-24 + 6i + -5iy + 7x = -7x + 7x

Combine like terms: -7x + 7x = 0
-24 + 6i + -5iy + 7x = 0

The solution to this equation could not be determined.

See similar equations:

| 16x^2-64x+48=0 | | c^2+7c+10=0 | | (2x+7)(x^2+2x-3)=0 | | -7c=-56 | | 2t-3t+8=3+-8 | | -1.25+.15x=0 | | 169=x^2+x^2+14x+49 | | 3x+5=-103-9x | | h=-16t^2+96t+4 | | 64b^2-121=0 | | 156-6x=3x+21 | | 4+6x-9x=3x | | b^2-4=0 | | 0.3b=8.1 | | 45x^6+18x^4-80x^2-32=0 | | -3z=72 | | 5x^2+19x-30=0 | | -5x+4(-5x+1)=129 | | 360=-18n | | 68-6x=9x+23 | | 8m^2-10m-3=0 | | b=9(1-b) | | 4c^2+15c-4=0 | | 6x+6=86-2x | | 48=16x | | 5y(y)(5y-1)+(2)5y-1= | | 15x=-225 | | 12x^3-38x+26=0 | | 15x=-132 | | 17lb=102 | | 2(x+3)=6x-4 | | x^2=-28x |

Equations solver categories